Honest Growth Pays Off: Understanding the Powerful Impact of Corruption Control on Businesses - Amrie Firmansyah; Nafis Dwi Kartiko (Jurnal Dinamika Akuntansi dan Bisnis, 2026)
This study examines the impact of state-level corruption control on firm growth in the Indonesian energy sector. Using 82 energy firms listed on the Indonesia Stock Exchange during 2002-2023, this study applies Ordinary Least Squares (OLS) regression with robust standard errors and fixed-effects estimation. Firm-level financial data are obtained from corporate financial statements, while corruption control indicators are sourced from the World Bank's Worldwide Governance Indicators. The results show that stronger corruption control is consistently associated with higher firm growth across multiple proxies. These findings indicate that improved institutional quality reduces uncertainty and supports more efficient resource allocation.